SISTEM INFORMASI SMP NEGERI 38 KABUPATEN TEBO: Middle School Information System Application;Web. - Suana, Irma (LP2M Universitas Nurdin Hamzah, 2021)
This Thesis Writing aims to facilitate the school in the follow-up actions that will be taken in informing the junior high school, where the previous system the school wrote the junior high school information on the ledger or agenda, then kept it in the file cabinet. The research method used in this thesis is to collect descriptive, the procedure of making this system is begun with analysis, system design, data collection, data analysis, design / design testing, implementation, analyzing the running system and making the system with descriptive methods, using programming languages web and database using SQLyog.This study produced an information system on public junior high schools 38 districts. Tebo is more effective, facilitates the school in informing junior high school, as well as systematic reporting. In the future, the application of the system so that someone needs optimal data in managing junior high school information is specifically for using this system.